The Effect of Good Corporate Governance and Intangible Assets on Company Financial Performance through Company Size (Empirical Study of Banking Companies Listed on the Indonesia Stock Exchange 2018-2022) - Lasmaria Yohana Manalu; Endang Ruhiyat (Formosa Journal of Sustainable Research, 2024)
This study uses firm size as an intervening variable to investigate the relationship between intangible assets and sound corporate governance and a company's financial success. This study takes a quantitative approach, using a sample of banking companies. Annual financial reports from 2018 to 2022 that are posted on the Indonesia Stock Exchange (BEI) include secondary data. Over the course of the five-year study, which comprised 46 organizations as subjects and 20 samples, 100 yearly financial report data were collected. In this study, purposive sampling is employed. Gathering and evaluating data for descriptive statistics, model appropriateness testing, Path analysis, traditional assumption testing, coefficient of determination, and hypothesis testing constitutes data processing. The outcomes of statistics Experiments reveal that intangible assets and sound corporate governance do not affect a company's size at the same time. The company's size and effective corporate governance both have an impact on its financial performance. The financial performance of the company is unaffected by intangible assets. The Sobel test results demonstrate that the impact of intangible assets and sound corporate governance on a company's financial success cannot be mitigated by a company's size